The Eastern Caribbean Currency Union : Would a Fiscal Insurance Mechanism Mitigate National Income Shocks? - Cashin, Paul.; Lemus, Antonio (Washington, D.C. : International Monetary Fund, 2012)
This paper studies the nature of the shocks affecting the Eastern Caribbean Currency Union (ECCU), and examines whether a hypothetical Eastern Caribbean fiscal insurance mechanism could insure member countries of the union against asymmetric national income shocks. The empirical results suggest that a one dollar reduction in an ECCU member country's per capita personal income could trigger, through reduced income taxes and increased transfers, flows equivalent to about 7 percent of the initial income shock. Each member of the currency union could benefit as well, although the extent of shock mitigation differs across individual countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet